PENGARUH MANAJEMEN KELAS DAN KOMPETENSI GURU TERHADAP HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Amelia Rasyid; Darul Ilmi (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the effect of classroom management and teacher competence on elementary school students’ mathematics learning outcomes. Methods: This research employed a quantitative approach with a correlational design. The population consisted of fourth- and fifth-grade students from public elementary schools in Cluster IV, Kamang Magek District. A total of 117 students were selected through proportional random sampling. Data on classroom management and teacher competence were collected using questionnaires, while mathematics learning outcomes were obtained from school documentation. The data were analyzed using simple linear regression and multiple linear regression with the assistance of IBM SPSS Statistics version 26. Results: The findings revealed that classroom management had a positive and significant effect on students’ mathematics learning outcomes. Teacher competence also had a positive and significant effect on students’ mathematics learning outcomes. Simultaneously, classroom management and teacher competence had a significant effect on mathematics learning outcomes. Novelty: This study provides empirical evidence that classroom management and teacher competence jointly influence mathematics learning outcomes based on students’ perceptions at the elementary school level.